ASSESSMENT OF METHANE ESTIMATION FROM VOLATILE FATTY ACID STOICHIOMETRY IN THE RUMEN IN VITRO - Jayanegara, A.; Ikhsan, I.; Toharmat, T. (Diponegoro University, 2013)
Rumen microbes breakdown feed to produce volatile fatty acids (VFA), carbon dioxide, ammoniaand methane (CH4). Metabolic hydrogen in the form of reduced protons is used during CH4 formation aswell as during VFA synthesis. Therefore, VFA concentration in the rumen may stoichiometrically berelated to CH4 emission. The aim of this study was to evaluate methane emission between experimentaland model estimates. Two stoichiometrical models for predicting CH4 from VFA were assessed, i.e.Moss et al. (2000) and Hegarty and Nolan (2007) models. The data sets were obtained from a publishedliterature. Samples used were leaves from 27 tropical plant species. Prediction error was conducted bycomputing root mean square prediction error (RMSPE). Results showed that estimation model of Mosset al. (2000) had lower RMSPE value, i.e. 8.01%, than that of Hegarty and Nolan (2007) model, i.e.10.73%. Variation of methane emission, i.e. the low or high methane can be estimated by VFAcomposition with a sufficient accuracy. Adjusment by considering H2 recovery lowered the biassignificantly. It can be concluded that Moss model had better accuracy in predicting CH4 emission fromVFA composition than that of Hegarty and Nolan model.